Employment Generation, Rural Infrastructure Development, Soil Water Conservation and Forest Protection with the Help of JFMC's - Saha, Sanjit Kumar (Indian Forester, 2016)
During the month of September, 2014 to March, 2015 few durable, semi-durable rural infrastructures were developed as part of the Joint Forest Management support activity. Assets viz. irrigation channel, rural road, rock check dam, water hole, contour trench were created based on the need of the local people and availability of the local natural resources to improve the socio-economic condition of the rural people, to conserve the nature and natural resources and above all to protect the forest and biodiversity in a joint, participatory and sustainable way with the help of Joint Forest Management Committee people. This work encourages the existing Forest Protection Committees to enhance their participation in forest management with the help of field foresters.